Effect of antituberculous drugs on human polymorphonuclear leukocyte functions in vitro - OKUYAN, BETÜL; SOYOĞUL GÜRER, ÜMRAN (ELSEVIER SCIENCE BV, 2005)
The aim of the study was to investigate antituberculous drugs effects on polymorphonuclear leukocyte (PMN) functions (phagocytic activity and intracellular killing activity) in vitro. PMNs obtained from healthy volunteers were incubated with antituberculous drugs (isoniazid [INH], rifampin [RIF], pyrazinamide [PZA], ethambutol [EMB], streptomycin [S], amikacin [A], ofloxacin [OFLX], prothionamide [PTH] and cycloserine [CyC]) and different combinations at therapeutic serum concentrations. Phagocytic activity of PMNs was significantly increased when compared with controls by PTH (p<0.001), A (p<0.001), OFLX (p<0.001), INH+RIF+S combination (p<0.01), A+OFLX combination (p<0.05), A+OFLX+CyC combination (p<0.01) and A+OFLX+CyC+PTH+EMB combination (p<0.01). Intracellular killing activity of PMNs was significantly increased by OFLX when compared with the control (p<0.05). No significant difference was observed in functions of PMN for other drugs when compared with control (p>0.05). Functions of PMN were significantly increased by OFLX when compared with A+OFLX combination (p<0.05). Phagocytic activity of PMNs was significantly increased by A+OFLX+CyC combination and A+OFLX+CyC+PTH+EMB combination when compared with A+OFLX+CyC+PTH combination and A+OFLX+CyC+PTH+PZA combination (p<0.05). No significant difference was found in functions of PMN between the other groups (p>0.05). In conclusion, some antituberculous drugs alone or in combination enhanced PMN functions, although in combination no additive or synergistic effects were detected. Moreover, none of the antituberculous drugs alone or in combination significantly decreased PMN functions. The drugs having adverse effects on immune functions would better be replaced with equally effective drugs or drug combinations having positive effects on PMN functions. (C) 2005 Published by Elsevier B.V.
Keywords: polymorphonuclear leukocyte; antituberculous drugs; phagocytosis; intracellular killing; PULMONARY TUBERCULOSIS; AMINOGLYCOSIDE ANTIBIOTICS; PHAGOCYTE FUNCTIONS; NEUTROPHIL FUNCTION; AGENTS; INVITRO; CHEMILUMINESCENCE; SERUM